2021
DOI: 10.1098/rsos.211255
|View full text |Cite
|
Sign up to set email alerts
|

Monkey see, monkey feel? Marmoset reactions towards conspecifics' arousal

Abstract: Consolation has been observed in several species, including marmoset monkeys, but it is often unclear to what extent they are empathy-based. Marmosets perform well in at least two of three components of empathy-based consolation, namely understanding others and prosociality, but it is unknown to what extent they show matching with others. We, therefore, tested whether non-aroused individuals would become aroused themselves when encountering an aroused group member (indicated by piloerection of the tail). We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 63 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…Among adults, marmosets observing the fear-related signal "piloerection of the tip of the tail" in others showed higher rates of affiliative behaviors (de Boer, Overduin-de Vries, Louwerse, & Sterck, 2013). In a follow-up study, de Oliveira Terceiro, Willems, Araújo, and Burkart (2021) found that naïve marmosets who encountered a group member displaying this fear signal preferentially approached this distressed individual even when not aroused themselves. Intriguingly, a similar pattern was also found in voles and could directly be linked to cooperative breeding and oxytocin.…”
Section: Introductionmentioning
confidence: 99%
“…Among adults, marmosets observing the fear-related signal "piloerection of the tip of the tail" in others showed higher rates of affiliative behaviors (de Boer, Overduin-de Vries, Louwerse, & Sterck, 2013). In a follow-up study, de Oliveira Terceiro, Willems, Araújo, and Burkart (2021) found that naïve marmosets who encountered a group member displaying this fear signal preferentially approached this distressed individual even when not aroused themselves. Intriguingly, a similar pattern was also found in voles and could directly be linked to cooperative breeding and oxytocin.…”
Section: Introductionmentioning
confidence: 99%